Financing development, financing constraint and R&D investment of strategic emerging industries in China - Xu, Ke; Geng, Chengxuan; Wei, Xiaoshu; Jiang, Huifeng (Journal of Business Economics and Management, 2020)
Taking listed companies of strategic emerging industries as the research subject, this paper uses KZ index to measure the degrees of financing constraints and financial intermediary as well as the stock market to represent the level of financial development. Then empirical models are constructed to analyse whether financial development can alleviate the financing constraints of R&D investment or not. Finally, the paper further investigates the interaction of financial development and firm characteristics (including firm size, ownership nature and establishment time) on the impact of R&D investment. The results show that the degree of financing constraint is negatively correlated with R&D investment. Both the development of financial intermediary and stock market play an important role in alleviating the R&D financing constraints, and the development of the stock market can better alleviate the R&D financing constraint. Moreover, the development of financial intermediary and stock market plays a heterogeneous role among enterprises of different size, nature and time of establishment. In order to achieve the 13th Five-year Plan target of strategic emerging industries in China, the government and enterprises need to work together to improve the financial development level and reduce information asymmetry, so as to expand the investment channels of R&D investment and improve their innovation capability and competitiveness.